2012
DOI: 10.4103/2319-4170.106140
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of anaplastic lymphoma kinase overexpression and the EML4-ALK fusion gene in non-small cell lung cancer by immunohistochemical study

Abstract: Background:Recently the echinoderm microtubule-associated protein-like 4-anaplastic lymphoma kinase (EML4-ALK) fusion gene with transforming activity was identified in non-small cell lung cancer (NSCLC). In addition, NSCLC patients with the EML4-ALK fusion gene had a dramatic response and longer progression free survival after ALK inhibitor treatment than those without this fusion gene. However, the incidence and clinical and molecular characteristics of the EML4-ALK fusion gene in NSCLC patients of Taiwan are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Besides chromosome rearrangements, gene overexpression has been described as the relevant abnormal alterations in the ALK gene in neuroblastoma, lung, and oesophageal cancer [22][23][24]. Chen et al (2012) also showed ALK overexpression in non-small cell lung cancer detected by immunohistochemical techniques [25]. Another recent evidence demonstrated that the ovarian high-grade serous carcinoma (HGSC) had significantly higher cytoplasmic ALK expression without chromosomal rearrangement or gene alterations compared to non-HGSC ovarian carcinomas [26].…”
Section: Discussionmentioning
confidence: 99%
“…Besides chromosome rearrangements, gene overexpression has been described as the relevant abnormal alterations in the ALK gene in neuroblastoma, lung, and oesophageal cancer [22][23][24]. Chen et al (2012) also showed ALK overexpression in non-small cell lung cancer detected by immunohistochemical techniques [25]. Another recent evidence demonstrated that the ovarian high-grade serous carcinoma (HGSC) had significantly higher cytoplasmic ALK expression without chromosomal rearrangement or gene alterations compared to non-HGSC ovarian carcinomas [26].…”
Section: Discussionmentioning
confidence: 99%